Established Stem Cell Model of Spinal Muscular Atrophy Is Applicable in the Evaluation of the Efficacy of Thyrotropin-Releasing Hormone Analog. (18th December 2015) - Ohuchi, Kazuki; Funato, Michinori; Kato, Zenichiro; Seki, Junko; Kawase, Chizuru; Tamai, Yuya; Ono, Yoko; Nagahara, Yuki; Noda, Yasuhiro; Kameyama, Tsubasa; Ando, Shiori; Tsuruma, Kazuhiro; et al.
Abstract : A human spinal muscular atrophy (SMA)-derived induced pluripotent stem cell (iPSC) disease model was established. The neural differentiation of SMA-iPSCs shortened the dendrite and axon length and increased apoptosis of the spinal motor neurons. This human in vitro disease model stimulated SMA pathology and revealed the potential efficacy of thyrotropin-releasing hormone (TRH) analog treatment for SMA. Novel therapeutic drugs can be screened easily and effectively using the human SMA-iPSC model. Abstract: : Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder characterized by the degeneration of spinal motor neurons. This disease is mainly caused by mutation or deletion of the survival motor neuron 1 ( SMN1 ) gene. Currently, no effective treatment is available, and only symptomatic treatment can be provided. Our purpose in the present study was to establish a human SMA-derived induced pluripotent stem cell (SMA-iPSC) disease model and assay a therapeutic drug in preparation for the development of a novel treatment of SMA. We generated iPSCs from the skin fibroblasts of a patient with SMA and confirmed that they were pluripotent and undifferentiated. The neural differentiation of SMA-iPSCs shortened the dendrite and axon length and increased the apoptosis of the spinal motor neurons. In addition, we found activated astrocytes in differentiated SMA-iPSCs. Using this model, we confirmed that treatment with the thyrotropin-releasing hormone (TRH) analog, 5-oxo-l -prolyl-l -histidyl-l -prolinamide, which had marginal effects in clinical trials, increases the SMN protein level. This increase was mediated through the transcriptional activation of the SMN2 gene and inhibition of glycogen synthase kinase-3β activity. Finally, the TRH analog treatment resulted in dendrite and axon development of spinal motor neurons in differentiated SMA-iPSCs. These results suggest that this human in vitro disease model stimulates SMA pathology and reveal the potential efficacy of TRH analog treatment for SMA. Therefore, we can screen novel therapeutic drugs such as TRH for SMA easily and effectively using the human SMA-iPSC model. Significance: Platelet-derived growth factor (PDGF) has recently been reported to produce the greatest increase in survival motor neuron protein levels by inhibiting glycogen synthase kinase (GSK)-3β; however, motor neurons lack PDGF receptors. A human in vitro spinal muscular atrophy-derived induced pluripotent stem cell model was established, which showed that the thyrotropin releasing hormone (TRH) analog promoted transcriptional activation of the SMN2 gene and inhibition of GSK-3β activity, resulting in the increase and stabilization of the SMN protein and axon elongation of spinal motor neurons. These results reveal the potential efficacy of TRH analog treatment for SMA.